(untitled) (Journal of Tropical Pharmacy and Chemistry, 2012)
The research about influent the use of cempedak seed starch (Arthocarpus champeden Lour) as a binder to the physical properties of paracetamol tablet in wet granulation has been conducted. Cempedak seed starch can improve the quality of materials, increase the viscosity, gelation ability, rehydration ability and increase the solubility. Paracetamol tablet be made in three formulas, with various concentration binders formula FA 6%, FB 8% and FC 10%. The resulting granules and tablets were evaluated. Granule evaluation includes fluiditas test and moisture content. Tablet evaluation includes uniformity of weight test, uniformity of size, hardness test and disintegration test. Granule evaluation results show that all formulas has qualified, except granule formula FA wich contain moisture 1.78%. Tablet evaluation results show that all formulas has qualified FI Ed. IV. Whereas for hardness test, tablet formula FA not eligible because it has hardness 3.8 Kg/cm2. The results of this research indicate that cempedak seed starch can be used as a binder in the manufacture of wet granulation paracetamol tablets. The higher the concentration used cempedak seed starch, than produced a good tablet. Cempedak seed starch can be used as a binder in concentration 8% and 10%.